Post-transplant CFHR5 mutation-related atypical HUS: The need for pre-transplant diagnosis - Mehta, Bhavana Asit; Dalal, Sonal Sanjiv; Kotecha, Udya; Shah, Sandip Chandrakant; Murnal, Ankita (Indian Journal of Case Reports, 2024)
Atypical hemolytic uremic syndrome (aHUS) is a rare form of thrombotic microangiopathy (TMA) affecting multiple organs and can be sporadic or familial. It is most commonly caused by dysregulation of the alternative complement pathway. aHUS can occur at any age with a high rate of progression to end-stage kidney disease. We describe the case of a 24-year-old man with chronic kidney disease, severe hypertension, and antineutrophilic antibody by IF positive. On biopsy, diffuse global glomerulosclerosis with TMA and IF findings of full house pattern suggestive of lupus nephritis were present. Considering a lupus nephritis case, after 2 years of hemodialysis underwent live-related renal transplant (Father Donor). Immediate post-transplant period developed severe cortical necrosis and TMA. An etiological workup was done to ascertain the cause of post-transplant TMA. After excluding common causes of antibody-mediated rejection (C4d and donor-specific alloantibody neg), calcineurin inhibitor toxicity, and infection, we detected an abnormal complement CFHR5 mutation with an autosomal dominant pattern of inheritance. Pre-transplant diagnosis could have prevented taking the kidney from the father for transplant and further prevented recurrence. Systemic lupus erythematosus and TMA both can have alternate complement pathway dysregulation leading to full house IF pattern and misdiagnosis.